Analysis of Maqasid Shari’ah on Religious Court Decisions on the Granting of Compulsory Wills to Non-Muslim Heirs - Palasenda, Nabil; Kamila, Aghisna Cahya; Nurfuadi, Fahmi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The matter of interfaith inheritance in Indonesia poses a multifaceted legal dilemma, especially with the judicial enforcement of wasiat wajibah (compulsory wills) for non-Muslim beneficiaries. This paper contextualizes Indonesia's legal framework within a broader comparative analysis, examining judicial discretion, legal diversity, and ijtihad as strategies for legal adaptation Purpose: This study aims to analyze whether the application of compulsory wills in judges' decisions against non-Muslim heirs contains elements of sharia maqasid Methods: A qualitative normative approach is employed, focusing on case law analysis and Maqasid Shari’ah principles. The study systematically analyzes court decisions, legal documents, and secondary literature to evaluate the legal reasoning behind the granting of wasiat wajibah to non-Muslim heirs. The research includes two key cases: Tebing Tinggi Religious Court Case No. 9/Pdt.P/2008/PA.Ttd and Surabaya Religious Court Case No. 473/Pdt.P/2010/PA.Sby, selected based on their legal significance and precedent-setting nature Results: The findings indicate that Indonesian courts’ application of wasiat wajibah to non-Muslim heirs aligns with Maqasid Shari’ah, particularly in preserving life (hifz al-nafs) and property (hifz al-mal). Judicial reasoning often relies on kinship considerations, legal adaptation through ijtihad, and social justice principles. However, the study identifies inconsistencies in how Maqasid Shari’ah is applied, with courts sometimes using it as a justification rather than an active tool for legal development. Implication: that courts should develop a more structured approach to integrating Maqasid Shari’ah in inheritance rulings. Furthermore, Indonesia’s model of using wasiat wajibah for non-Muslim heirs provides a legal precedent that could inform similar cases in other jurisdictions dealing with interfaith inheritance disputes Originality: This study introduces a jurisprudential perspective that integrates judicial discretion, legal pluralism, and ijtihad developments in Islamic courts. Unlike previous research that focuses solely on doctrinal analysis, this study critically examines how Maqasid Shari’ah is operationalized in judicial decision-making